Study of ISO 9001:2015 Quality Management System Implementation in RTG Pad Manufacturing Project at Perawang Port - Harahap, Ido Rizky; Hasibuan, Ghina Chitya Raphita; Anas, Ridwan (Universitas Ibn Khaldun Bogor, 2025)
ISO or (International Organization for Standarization) is a worldwide non-governmental organization with representatives in many countries that creates and disseminates standards in the commercial, industrial and proprietary fields. The ISO organization itself was founded in Geneva, Switzerland in 1947. The construction industry in Indonesia continues to experience rapid development. The number of construction projects causes more and more construction service companies to develop and causes increasingly fierce competition between construction service companies (Contractors). Increased competition between companies makes companies aware of quality. One of the important requirements is the ownership of ISO 9001 Certificate. This study aims to determine the level of implementation of a quality management system based on ISO 9001: 2015, constraints that occur in the implementation of the ISO 9001: 2015 quality management system and strategies to improve the implementation of the ISO 9001: 2015 quality management system in the RTG Pad Manufacturing project at Perawang Port. In this study the method used is a quantitative method that is descriptive. Data is collected through questionnaires so that it is expected to obtain accurate data on the implementation of the quality management system. From the results of data analysis of the implementation of the ISO 9001: 2015 quality management system in the RTG Pad Manufacturing project at Perawang Port, it was found that the implementation level was 81.09% in the